Conceptualization of Women Empowerment Through 5S Approach: Complementary for Sustainable Development. - Soharwardi, Mariam Abbas (International Journal on Women Empowerment, 2023)
Background: For promoting the gender equality in the modern era, women's empowerment becomes extremely important. Empowerment gives women the ability to participate in decision-making processes that affect their livelihood in a productive and effective way. When women have a say in daily chores, management of their household expenditure, resource allocation, and community development, it leads to more inclusive and sustainable practices. Women's involvement in decision-making also ensures that their needs, priorities, and perspectives are taken into account. Methodology: There are numerous definitions and aspects of women's empowerment in literature; however, in the current study, 5S Approach is used to explored and conceptualize the women's empowerment. These five S's stand for self-esteem, self-efficacy, self-confidence, self-management, and self-decision. If a woman is able to achieve all five of these skills, she will be able to live and move through society as she deems fit. The prerequisites and outcome of empowerment are these 5S. This 5S approach aims to identify and manage women's self-empowerment by their own volition. Results: Many women in poor and impoverished nations lack self-awareness; therefore, it is necessary to empower all women, make them capable of doing so, and make them aware of their respect for and commitment to their beliefs. By applying these 5S approach we can be able to empower the women from every aspect of their capabilities to make their lives worth full and valuable and covering the gender gap. Conclusion: When women take control of their lives through 5S approach, they become more capable of taking on powerful roles and leadership positions within society—ultimately empowering not just individual households but entire communities to rise out of poverty and desperation. So, for every woman who desires a better future for herself or her family, as long as her self-awareness is essential in forging a brighter path for sustainable development.